ANALYSIS OF USING SUSTAINED SILENT READING STRATEGY TOWARD STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT - Dini Hidayati; Dhania Haura Griselda (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2023)
The objective of this study is to examine the efficacy of implementing the Sustained Silent Reading approach as a means to enhance students' proficiency in comprehending descriptive texts within the context of English language learning. The participants of this study were selected from a specific group of pupils in Class X at 1 Public High School Metrokibang who had previously demonstrated a limited comprehension of descriptive literature. The researcher employed qualitative methodologies to examine various subjects, employing a combination of purposive sampling, direct observation, and structured interviews with the designated participants. The interview procedure entails the posing of four inquiries by students, to which students thereafter provide responses in their capacity as informants or subjects. Based on the present investigation, it was determined that pupils encountered challenges in comprehending the English language due to the inadequacy and inefficiency of the employed instructional approaches. The implementation of the collaborative reading technique in the classroom setting may lead to less focus among students, hence hindering their comprehension of English descriptive texts. However, the implementation of the Sustained Silent Reading approach in educational settings has been found to enhance students' comprehension of descriptive literature, hence improving their overall reading comprehension skills. Hence, it was determined by the researcher that the utilisation of this approach has the potential to enhance students' comprehension of descriptive text and foster a heightened level of engagement in the learning process